2004
DOI: 10.3171/jns.2004.100.3.0560
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and electrical stimulation of the auditory cortex for intractable tinnitus

Abstract: Tinnitus is a distressing symptom that affects up to 15% of the population for whom no satisfactory treatment exists. The authors present a novel surgical approach for the treatment of intractable tinnitus, based on cortical stimulation of the auditory cortex. Tinnitus can be considered an auditory phantom phenomenon similar to deafferentation pain, which is observed in the somatosensory system. Tinnitus is accompanied by a change in the tonotopic map of the auditory cortex. Furthermore, there is a highly posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 23 publications
1
108
0
Order By: Relevance
“…However, if the subsequent rTMS applied to the site of maximal TI-related activity is successful in reducing TI, then this finding increases confidence that this cortical site plays a causal role in TI." We provide only two examples of this approach (Plewnia et al, 2007 andde Ridder et al, 2004). We conclude this section on page 20 by saying "Although requiring replication, these two rTMS studies point to the essential role of auditory cortex and regions of multisensory integration in the perception of TI."…”
Section: Specific Commentsmentioning
confidence: 94%
See 2 more Smart Citations
“…However, if the subsequent rTMS applied to the site of maximal TI-related activity is successful in reducing TI, then this finding increases confidence that this cortical site plays a causal role in TI." We provide only two examples of this approach (Plewnia et al, 2007 andde Ridder et al, 2004). We conclude this section on page 20 by saying "Although requiring replication, these two rTMS studies point to the essential role of auditory cortex and regions of multisensory integration in the perception of TI."…”
Section: Specific Commentsmentioning
confidence: 94%
“…When rTMS was subsequently targeted to this site, six patients reported TI relief. In an earlier case study, de Ridder et al (2004) reported a relative reduction in the right auditory cortical response to music presented binaurally. While this result is consistent with the left-sided laterality of the hearing loss, de Ridder and colleagues claim that the result also supports the conclusion that TI-related activity was greater on the side contralateral to (leftsided) TI.…”
Section: Suppression Of Ti Using Direct Neural Stimulationmentioning
confidence: 94%
See 1 more Smart Citation
“…Years later Sinha et al (2005) observed, in a single chronically implanted patient, that electrical stimulation of the surface of the left posterolateral STG resulted in reversible, moderate hearing loss in the right ear. In what may be a related phenomenon, it has also been reported that tinnitus is suppressed by electrical stimulation of posterolateral STG (de Ridder et al, 2004) and by repetitive transcranial magnetic stimulation (rTMS) directed toward temporal-parietal cortex (Plewnia et al, 2003). These observations raise the possibility that temporal lobe cortical stimulation might be an effective treatment for patients with intractable tinnitus.…”
Section: Introductionmentioning
confidence: 95%
“…Drouot et al 8 suggested a sequential pattern between 1 and 3 V for the analgesic stimulation. De Ridder et al 9 proposed continuous mode and long stimulation for the tinnitus treatment. The programming for the stimulation, at first, followed our experience in analgesic stimulation.…”
Section: Follow-upmentioning
confidence: 99%